Cost-Accounting: Principles and Managerial Applications. - Fisher, Paul A.; Spiller, Earl A. (The Accounting Review, 1975)
Abstract Reviews the book "Cost Accounting: Principles and Managerial Applications," 3rd ed., by Gerard R. Crowningshield and Kenneth A. Gorman.